Implementation of Principles of Multimedia Design into learning objects: Audio Narration perception - Ling Slew, Woei; Yuen May, Chan (2008)
Clark and Mayer (2003) had conducted various studies regarding how people learn and how multimedia could be combined effectively to facilitate learning [1]. Clark and Mayer's Six Principles of Multimedia Design were adopted as a guideline during the development of a set of learning objects for a procedural-based course on 54 students over a period of 10-weeks. This study explored the potential of multimedia learning objects and reported that the students reacted enthusiastically to it, showing acceptance of using it as the learning materials. The students are also reported to be able to perform the tasks upon completion. This study also re-affirmed that the redundancy principle as proposed by Clark and Mayer will not affect the students' cognition due to the students' language proficiency.